2007
DOI: 10.1111/j.1462-2920.2007.01455.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of aerobic microbial communities and soil respiration to water‐level drawdown in a northern boreal fen

Abstract: On a global basis, peatlands are a major reserve of carbon (C). Hydrological changes can affect the decomposition processes in peatlands and in turn can alter their C balance. Since 1959, a groundwater extraction plant has generated a water-level gradient at our study site that has gradually changed part of the wet fen into a dry peatland forest. The average water-level drawdown of the gradient (from a pristine 9 cm to 26 cm in the dry end) is close to an estimate predicted by an increase in mean global temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(71 citation statements)
references
References 78 publications
6
57
0
Order By: Relevance
“…Indeed, laboratory and field experiments have demonstrated that mass loss is higher under aerobic conditions than under anaerobic conditions [Belyea, 1996;Scanlon and Moore, 2000;Yavitt et al, 2000;Blodau et al, 2004;Laiho, 2006;Moore and Basiliko, 2006;Jaatinen et al, 2008;Wickland and Neff, 2008]. In Figure 3, mass losses from vascular plant litter and Sphagnum litter decomposing in parallel under aerobic and anaerobic conditions are compared.…”
Section: Litter Decomposition In Aerobic Versus Anaerobic Conditionsmentioning
confidence: 99%
“…Indeed, laboratory and field experiments have demonstrated that mass loss is higher under aerobic conditions than under anaerobic conditions [Belyea, 1996;Scanlon and Moore, 2000;Yavitt et al, 2000;Blodau et al, 2004;Laiho, 2006;Moore and Basiliko, 2006;Jaatinen et al, 2008;Wickland and Neff, 2008]. In Figure 3, mass losses from vascular plant litter and Sphagnum litter decomposing in parallel under aerobic and anaerobic conditions are compared.…”
Section: Litter Decomposition In Aerobic Versus Anaerobic Conditionsmentioning
confidence: 99%
“…True chimeric and clearly non-fungal or non-actinobacterial sequences were eliminated from further analyses. Phylogenetic analyses were conducted as in Jaatinen et al (2008).…”
Section: Microbial Community Analysesmentioning
confidence: 99%
“…The structure of the peatland microbial community varies with the plant community (Borgå et al, 1994;Fisk et al, 2003;Thormann et al, 2004;Jaatinen et al, 2007Jaatinen et al, , 2008, and it has been shown that changes in peatland hydrology affect both (Jaatinen et al, 2007;Peltoniemi et al, 2009). Microbial responses in the form of enzyme activities have been detected (Fenner et al, 2005a;Toberman et al, 2010) and may be directly induced by the increased availability of oxygen and/or changes in pH.…”
Section: Introductionmentioning
confidence: 99%
“…This alters the functioning and surface structure of the peatland, increasing the aerated volume of the surface peat where rapid decomposition is possible (Freeman et al, 2001;Jaatinen et al, 2008) and causing subsidence of the soil first by physical compression, removing the supporting pressure of the water and then by the increased decomposition of the surface peat layers (Minkkinen & Laine, 1998;Jaatinen et al, 2008).…”
Section: Exploitation Of Peatlandsmentioning
confidence: 99%